(untitled) (Revista Argentina de Musicología, 2018)
This article examines some of the mechanisms through which the composer Alberto Williams managed to insert himself into the national canon as “the patriarch of Argentinian music”. We will follow Dahlhaus, who proposes that the criteria for “authenticity” (of nationalism) can be found in historical processes and functions rather than in the aesthetic criteria of composition. In this context, the study of La Quena (1919-1936) –a largely unexplored source that promoted activity of the Conservatorio de Música de Buenos Aires– attempts to answer questions that go beyond the traditional field of music production. In this paper, we attempt to show that Williams’ place in the canon has most likely been generated by the articulation of a dual mechanism of legitimation: first, the founding and management of the Conservatorio de Música de Buenos Aires; second, the use of the press. In this sense, just as Anderson emphasizes the importance of the press’s role in the formation of a nationalist consciousness in the “Imagined Communities”, we too consider that, in Williams’ personal trajectory, the road to recognition may have been touched by the indelible mark of the press –the metonymy of nationality and modernity–.